Pregnant Smokers Receiving Opioid Agonist Therapy Have an Elevated Nicotine Metabolite Ratio: A Replication Study. Issue 10 (18th April 2020) - Kranzler, Henry R; Washio, Yukiko; Zindel, Leah R; Lynch, Kevin G; Hand, Dennis; Tyndale, Rachel F; Oncken, Cheryl; Schnoll, Robert
Abstract: Introduction: Pregnant women exposed chronically to opioids smoked more cigarettes per day (CPD) and had a higher nicotine metabolite ratio (NMR), 3-hydroxycotinine/cotinine, a biomarker of nicotine metabolism and clearance, than those not receiving opioids. We examined CPD and NMR in a group of pregnant smokers, a quarter of whom were receiving opioid agonist therapy (OAT). Aims and Methods: Pregnant smokers recruited to participate in a placebo-controlled trial of bupropion for smoking cessation provided a blood sample for measurement of NMR. Results: Half (52.4%) of the 124 women with NMR data were African American. OAT-treated women ( n = 34, 27.4%; 27 receiving methadone and 7 buprenorphine) were more likely to be white (79% vs. 30%, p < .001) and to have a lower mean PHQ-9 total score (2.91 [ SD = 2.83] vs. 4.83 [ SD = 3.82], p = .007). OAT-treated women reported smoking more CPD (9.50 [ SD = 5.26] vs. 7.20 [ SD = 3.65], p = .005) and had higher NMR (0.78 [ SD = 0.36] vs. 0.56 [ SD = 0.25], p = .001) than the non-OAT-treated group. In a linear regression analysis adjusting for race, depression severity, and CPD, NMR was greater in the OAT group ( p = .025), among whom the daily methadone-equivalent dosage correlated with NMR (Spearman's ρ = 0.49, p = .003). Conclusions: Consistent with the findings of Oncken et al. (2019), we found that OAT smokers smoked more and had higher NMR than non-OAT smokers. As higher NMR is associated with a reduced likelihood of smoking cessation, the effects on NMR of both pregnancy and OAT could contribute to a lower smoking cessation rate in pregnant smokers receiving chronic opioid therapy. Implications: We replicated the finding that the NMR is significantly greater among pregnant smokers receiving OAT than those not receiving this treatment for opioid use disorder. Furthermore, we found that the dosage of the OAT was significantly associated with the NMR level. These findings may contribute to a poorer response to smoking cessation treatment in pregnant women treated with OAT, particularly those receiving high-dose therapy, and raise the question of whether novel approaches are needed to treat smoking in this subgroup of pregnant smokers.